Road races and social media - a snapshot in 2015 - Punzi, A. (New Studies in Athletics, 2015)
In recent years the social media have become an increasingly important element of the overall media environment. Based on personal observations of the various social media channels and study of publically available publications, this report provides a snapshot of how running road race organisers currently use the social media to support their marketing efforts. It includes a short history of when organisations in the running industry embraced social media, an explanation of why social media and running races are intertwined, examples of the interactions between races and runners on social media, a discussion of how social media activity can be evaluated and outlines of new trends in this field. The author concludes that the social media have become important, if not essential, tools for race organisers. He also calls for more systematic and detailed research to help ensure that race organisers are making best use of the opportunities provided by social media and can improve their work in the future.